Urinary proteomics to diagnose chronic active antibody-mediated rejection in pediatric kidney transplantation: a pilot study - Kanzelmeyer, Nele; Fichtner, Alexander; Krupka, Kai; Tönshoff, Burkhard (Transplant international, 2019)
Chronic antibody-mediated rejection (cABMR) is the main cause of long-term renal graft loss. Late-stage diagnosis is made by detecting donor-specific antibodies (DSA) in blood combined with typical histomorphological lesions in renal allografts. There is a need for noninvasive biomarkers for cABMR that might permit screening and earlier diagnosis. In a case control study of 24 pediatric renal transplant recipients, urine samples were analyzed using capillary electrophoresis and mass spectrometry. Patients were matched with 36 pediatric renal transplant patients without cABMR. Statistical analysis used the nonparametric Wilcoxon test to identify 79 significant biomarkers, which were combined to a support vector machine-based classifier. After validation in an independent test cohort of eight pediatric patients with and 12 without cABMR, the area under the receiver operating characteristic (ROC) curve (AUC) for detection of cABMR was 0.92 (95% CI 0.71-0.99) with a sensitivity of 100% (95% CI 63-100%) and a specificity of 75% (95% CI 43-95%). Combining this classifier with the urinary proteomic marker CKD273 improved the detection of patients with cABMR with misclassification in only 2/20 of the patients. These data indicate that a biomarker pattern derived from urinary proteomics allows the detection of cABMR in pediatric renal transplant recipients with high sensitivity and moderate specificity.
Published online: 12 November 2018
Gesehen am 22.07.2019